KOLABORASI INTERDISIPLINER DALAM PEMBELAJARAN BERBASIS PROYEK PADA SEKOLAH MENENGAH KEJURUAN: SENI TEATER DAN MATA PELAJARAN LAIN - Rin Surtantini; Eko Santoso (Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
Designing Project-Based Learning in the subjects of concentration in Vocational High Schoolwhich is integrated with other subjects has become a challenge for vocational high schoolteachers in the light of “Kurikulum Merdeka” implementation. The current article attempts tobe part of initiative contribution towards developmental trend of study, research, conceptualor practical ideas on Project-Based Learning (PjBL) in Vocational High School. The planningof collaborative PjBL process and the outline of PjBL integrated learning modules arepresented as a sample of PjBL design in the subject of Theater in collaboration with othersubjects in “Kurikulum Merdeka”. The steps in designing PjBL consist of (1) designingproduct or services; (2) making product or doing services; (3) controlling the quality; and (4)marketing product or services